2019
DOI: 10.1088/1748-9326/ab1ec7
|View full text |Cite
|
Sign up to set email alerts
|

Dry-hot magnitude index: a joint indicator for compound event analysis

Abstract: Weather and climate extremes, such as droughts and heat waves, have been commonly characterized by different properties, including frequency, duration, and magnitude. The magnitude is among the most important properties that determine the impact of extremes. Compound dry and hot events may cause detrimental impacts on water resources, energy security, crop production and food security, and have been receiving increasing attention in recent years. Although extensive studies have been conducted to investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 63 publications
2
43
0
Order By: Relevance
“…This suspects that the combined adverse effect of temperature and precipitation (i.e. drought) is playing a more detrimental role in agricultural productivity [55], than the individual impact of temperature extremes. The regional analysis on agricultural vulnerability showed that although few clusters of districts had favorable (unfavorable) conditions for the indicators, it eventually resulted in increased (decreased) agricultural vulnerability.…”
Section: Discussionmentioning
confidence: 99%
“…This suspects that the combined adverse effect of temperature and precipitation (i.e. drought) is playing a more detrimental role in agricultural productivity [55], than the individual impact of temperature extremes. The regional analysis on agricultural vulnerability showed that although few clusters of districts had favorable (unfavorable) conditions for the indicators, it eventually resulted in increased (decreased) agricultural vulnerability.…”
Section: Discussionmentioning
confidence: 99%
“…compound dry and hot events) (Seneviratne et al 2012, Leonard et al 2014, Liu et al 2017, Miralles et al 2018. Recent decades have witnessed multiple compound dry and hot events in different regions, such as Europe (2003), China (2006), Russia (2010), southern US (2011), and southern Africa (2015-2016) (Barriopedro et al 2011, Hoerling et al 2013, Flach et al 2018, Herring et al 2018, Wu et al 2019. The compound dry and hot event may lead to impacts larger than the sum of impacts from individual extremes and has attracted increased attention in recent decades (Seneviratne et al 2012, Kopp et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, we find that the climate factors considered in this study—capturing CEs during the growing season—explain nearly half of the variations in hop yield anomalies. Exposure to combinations of the four modes is better resolved through the analysis of daily variability, as opposed to using annual averages (Zscheischler et al ., 2017; Wu et al ., 2019). However, we assume that CEs only explain a part of the yield variability and that other factors, such as soil properties, management decisions and market factors, likely contribute to the remaining yield variations (e.g., Nesvada et al 2013; (Krofta et al ., 2013; Čeh, 2014); Kolenka et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Compound events may lead to amplified impacts on agricultural production compared to individual events and have received increased attention in recent years (Zscheischler et al ., 2017; Hao et al ., 2019; Potopová et al ., 2019a; Potopová et al ., 2020). The combination of multiple extreme climate events (CEs) is termed a compound event and often results from a combination of climatic events (Leonard et al ., 2014; Wu et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%